2014
DOI: 10.3945/ajcn.113.075663
|View full text |Cite
|
Sign up to set email alerts
|

Associations between red meat intake and biomarkers of inflammation and glucose metabolism in women

Abstract: Greater red meat intake is associated with unfavorable plasma concentrations of inflammatory and glucose metabolic biomarkers in diabetes-free women. BMI accounts for a significant proportion of the associations with these biomarkers, except for ferritin. Substituting red meat with another protein food is associated with a healthier biomarker profile of inflammatory and glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
153
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(172 citation statements)
references
References 46 publications
15
153
2
2
Order By: Relevance
“…sausage, cookies, biscuits, cake, pastries) [33], high-energy (e.g. sugar-sweetened) drinks [34,35], and processed meat [36,37] have been associated with pro-inflammatory properties. The results of diet analyses based on DII scores in the present study are consistent with those of previous studies addressing other cancer outcomes [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…sausage, cookies, biscuits, cake, pastries) [33], high-energy (e.g. sugar-sweetened) drinks [34,35], and processed meat [36,37] have been associated with pro-inflammatory properties. The results of diet analyses based on DII scores in the present study are consistent with those of previous studies addressing other cancer outcomes [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (16) showed that participants in the top quintile of dietary phosphatidylcholine intakes had a 34% (95% CI: 27%, 44%) higher risk of type 2 diabetes than those in the bottom quintile intakes; however, the study did not investigate the direct association of circulating TMAO with the risk of type 2 diabetes. Red meat is an important source of carnitine and choline, which are precursors to TMAO, and its consumption was associated with glucose metabolism (25,26) and an increased risk of type 2 diabetes (27)(28)(29)(30). Red meat contains other nutrients or compounds related to the development of type 2 diabetes (31,32), and, to our knowledge, whether TMAO is responsible for the association between consumption of red meat and risk of type 2 diabetes has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in developed countries such as the UK, U.S. and Latin Americas found that consumption of calories-rich food which mainly composed of protein and fat, especially red meat, increased the risk of chronic diseases such as gout, diseases of the pancreas type 2 diabetes, heart diseases [16] [17] [29], cancer (colon cancer, stomach cancer, kidney cancer [18] [30] and cardiovascular disease [16] [31].…”
Section: Discussionmentioning
confidence: 99%